2020
DOI: 10.3390/app10061918
|View full text |Cite
|
Sign up to set email alerts
|

Shared Tuned Mass Dampers for Mitigation of Seismic Pounding

Abstract: This study explores the effectiveness of shared tuned mass damper (STMD) in reducing seismic pounding of adjacent buildings. The dynamics of STMDs is explored through numerical simulations of buildings idealized as single and multiple degree of freedom oscillators. An optimization method proposed in the literature is revisited. It is shown that the optimization results in two different solutions. The first one corresponds to the device being tuned to one of the buildings it is attached to. The second solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Earthquakes have been and remain to be one of the prominent threats to the safety and serviceability of civil engineering structures and infrastructure systems. Numerous strategies have been proposed, researched, and implemented for seismic protection of structures [1][2][3][4]. e use of structural response control strategies has been proven to be an effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…Earthquakes have been and remain to be one of the prominent threats to the safety and serviceability of civil engineering structures and infrastructure systems. Numerous strategies have been proposed, researched, and implemented for seismic protection of structures [1][2][3][4]. e use of structural response control strategies has been proven to be an effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…One paper concerns the challenging task of designing lead rubber bearings considering different performance requirements [10]. The performance of some variants and improvements of the classical concept of tuned mass damper is also analyzed in various applications and configurations [6,8,12]. Novel dissipation devices are finally developed and analyzed from an experimental and a numerical point of view [5,7,9].…”
Section: Editorialmentioning
confidence: 99%
“…In paper [12], Rupakhety et al explore the effectiveness of shared tuned mass damper (STMD) in reducing seismic pounding of adjacent buildings. The authors carefully revisit the idea of STMD reported in a paper from the literature [Earthq.…”
Section: Editorialmentioning
confidence: 99%
“…e concept allows two dynamically similar and/or dissimilar structures to exert the forces upon one another for overall response reduction of the system. e available studies showed improved performance of the structural systems by connecting different passive control devices to limit the pounding actions under earthquake ground motions [14,[33][34][35][36][37][38][39]. Overall, the FDs have offered its potential in minimizing the extreme vibrations installed in a structure; however, research strategies have not been implemented to assess the response and quantify the effectiveness of the FDs for coupled adjacent buildings under both seismic and wind excitations.…”
Section: Introductionmentioning
confidence: 99%